Pengembangan Media Digital Audio Visual Berbasis Problem Based Learning (PBL) pada Pembelajaran Pendidikan Pancasila Kelas III Sekolah Dasar - Aulia Dinayanti; Nina Nurhasanah; Syarif Sumantri (STKIP Subang, 2026)
This study aims to develop an audio-visual digital learning media based on Problem Based Learning (PBL) in Pancasila Education on the topic “Rights and Obligations at School” for third grade elementary school students. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). This study involved media experts, material experts, and language experts, as well as trials conducted on third grade students at SDN Bintara Jaya 1, involving 3 students in the one-to-one trial, 10 students in the small group trial, and 28 students in the field test trial. The data collection technique used in this study was a quantitative descriptive approach, obtaining 96.7% from media experts, 92.67% from material experts, and 92.67% from language experts. The results of the one-to-one trial showed an average score of 97%, the small group trial showed an average of 92%, and the field test trial showed an average of 93%. These results indicate that the audio-visual digital learning media based on Problem Based Learning (PBL) achieved a “very good” category and is therefore considered feasible to be used as a learning media in Pancasila Education on the topic “Rights and Obligations at School” for third grade elementary school students.